FASILITAS PAJAK INVESTASI BARU, TARIF EFEKTIF DAN ALIRAN MASUK FDI STUDI KOMPARATIF ANTARA INDONESIA DENGAN AFRIKA SELATAN, MALAYSIA, THAILAND DAN VIETNAM - WILLIEM CHAHYA WIJAYA (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2013)
This Research is intended to make a comparative analysis of the income tax incentive that is provided by Indonesia, South Africa, Malaysia, Thailand and Vietnam and also to compare the feasibility of that incentive and the impact of that incentive to the foreign direct investment (FDI) growth. Object analysis in this research are income tax incentive, effective income tax percentage and percentage FDI to GDP. The comparative analysis method used in this research are the comparison of the income tax incentive provided by Indonesia compare with the income tax incentive provided by South Africa, Malaysia, Thailand and Vietnam. To compare the effective income tax percentage, this research use an ilustrative model that used the incentive provided by each country implemented to the model and measure the effect of that incentive to the income tax percentage in each country. Last, to make a comparison of the impact for income tax incentive to the investment especially for foreign investment, this research using the FDI growth and percentage FDI to GDP for each country. From this research, we could conclude that the income tax incentive that is implemented in Indonesia in 2007 are out of date because the other country already implemented the incentive in 2000 or 2001. And the income tax incentive implemented in Indonesia is also less eficiency in reduce the percentage income tax compared with South Afrika, Malaysia, Thailand and Vietnam.